Real estate as an efficient instrument for innovative activities of industrial enterprises in modern conditions - Byvsheva, L.; Kondratenko, O. (Економічний вісник Донбасу, 2018)
The article defines the factors of reengineering, which ensure the success and efficiency of business processes of an industrial enterprise. The necessity of implementation of reengineering of business processes in modern industrial enterprises according to the requirements of the environment is substantiated. In order to further develop the reengineering of business processes in Ukraine, a mechanism of implementation is proposed that will allow increasing the number of specialists in the given field and the awareness of enterprises of Ukraine about this method of managing processes in organizations. У статті визначено чинники реінжинірингу, що забезпечують успіх та ефективність бізнес-процесів промислового підприємства. Обґрунтовано необхідність впровадження реінжинірингу бізнес-процесів на сучасних промислових підприємствах в залежності від вимог зовнішнього середовища. Для подальшого розвитку реінжинірингу бізнес-процесів в Україні запропоновано механізм реалізації, що дозволить збільшити кількість фахівців даної сфери та проінформованість підприємств України про даний метод управління процесами в організаціях. В статье определены факторы реинжиниринга, которые обеспечивают успех и эффективность бизнес-процессов промышленного предприятия. Обоснована необходимость внедрения реинжиниринга бизнес-процессов на современных промышленных предприятиях в зависимости от требований внешней среды. Для дальнейшего развития реинжиниринга бизнес-процессов в Украине предложен механизм реализации, который позволит увеличить количество специалистов данной сферы и протнформированность предприятий Украины о данном методе управления процессами в организациях.